Development of a Module Based on Problem Based Learning (PBL) Model And Local Potential As Supporting Biodiversity Materials In Senior High School of SMA Negeri 1 Natal - Amelisa Putri; Kartika Manalu (Universitas Labuhanbatu, 2024)
One of the learning resources for biology is biodiversity. Region-specific biodiversity differs. Thus, in light of biodiversity, many students still struggle to comprehend the material covered in biology lectures, particularly at SMA Negeri 1 Natal.The research uses the ADDIE model research and development (R&D) method. The instrument of this research is a questionnaire sheet for material experts, media experts, teachers and students to test practicality and pre-test and post-test to test effectiveness. Class X MIPA-1 SMA Negeri 1 Natal students as test subjects. Testing was carried out on 30 students and biology teachers to see the practicality of the module using student and biology teacher response questionnaires. Based on the validation results from material experts, a percentage of 96.25% was obtained with the criteria